A new simple-lamina species of Polystichum (Dryopteridaceae) from Lingnan Region, China - Shang, Hui; Li, Jian-Ling; Li, Zhong-Yang; Shao, Wen; Li, Fang-Hua; Li, Dong; Liu, Hong-Mei; Jiang, Ri-Hong (Phytotaxa, 2025)
Polystichum ensiforme, a new polystichoid fern species from Guangxi Zhuang Autonomous Region, China, is described and illustrated. Morphologically, the new species most closely resembles P. basipinnatum but differs in having a generally simple lamina, scattered sori, and leathery lamina texture. Phylogenetic analysis placed it as an isolated clade within P. sect. Cyrtomiopsis. A key to the species of P. sect. Cyrtomiopsis is also provided.